Feminist Alliances - Burns, Lynda (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
This book is about feminism, its critics, and its possible directions for change. The nine chapters raise questions about theories of sexual difference, power, justice and history. A central theme concerns the prospects for combining feminist with other, non-feminist, political perspectives.